Gilberto Freyre : a experiência da escrita - Santos, Manuela Assunção (2009)
The present research aims to develop an analysis of the importance of formal aspects present in certain books by the anthropologist Gilberto Freyre such as his utilization of stylistic resources, biographical elements and oral narrative , as well as his tendency towards the essay gender, resulting from the influence of Hispanic authors.Moreover, from the study of both these formal aspects, and linkage with literature established by Freyre, as the theoretician, this research intends to further explore both, the interdisciplinarity and the empathic approach to his subjects of study. This empathic approach reveals the author´s specific epistemological reflection. The goal of this analysis of the interdisciplinarity treatment present in Freyre´s work, is to debate how far such strategies favor a mystification of history.